2012
DOI: 10.1177/1934578x1200700213
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiling of Constituents of Smilacis glabrae Using Ultra-high Pressure Liquid Chromatography Coupled with LTQ Orbitrap Mass Spectrometry

Abstract: A reliable LC-MS method has been applied for the separation and identification of major constituents of the rhizome of Smilacis glabrae. Identification of the constituents was carried out by interpretation of their retention time, and MS and MS/MS data, especially by comparing these with Sarcandra glabra under the same LC-MS conditions, as well as the data provided by the literature. Thirty-three compounds, including catechin derivatives, flavanonols, phenolic acid derivatives and phenylpropanoid glycosides we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…The components in the ethyl acetate extract were first analysed by the UHPLC‐Q‐TOF‐MS approach, and the results are provided in the Supporting Information Table S1. Except astilbin and isomers, engeletin, cinchonains, caffeoylshikimic acids, and other reported compounds from the literature (Chen et al ., ; Li et al ., ; Xu et al ., ), five molecular formulae of C 33 H 26 O 12 , C 25 H 20 O 10 , C 22 H 22 O 12 , C 22 H 22 O 11 and C 17 H 16 O 9 were also detected from this herb for the first time and were further investigated using MS/MS and on‐line LC‐SPE‐NMR‐MS methods.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The components in the ethyl acetate extract were first analysed by the UHPLC‐Q‐TOF‐MS approach, and the results are provided in the Supporting Information Table S1. Except astilbin and isomers, engeletin, cinchonains, caffeoylshikimic acids, and other reported compounds from the literature (Chen et al ., ; Li et al ., ; Xu et al ., ), five molecular formulae of C 33 H 26 O 12 , C 25 H 20 O 10 , C 22 H 22 O 12 , C 22 H 22 O 11 and C 17 H 16 O 9 were also detected from this herb for the first time and were further investigated using MS/MS and on‐line LC‐SPE‐NMR‐MS methods.…”
Section: Resultsmentioning
confidence: 97%
“…The fragmentation ion loss of CO ( m / z 451.1022) was observed as the main peak in the MS/MS spectrum (Fig. B), and another main fragmentation ion of m / z 341.0654 was the characteristic ion of cinchonains, in which the ion was produced from the loss of 3,4‐dihydroxyphenyl group (Li et al ., ). Thus, they were deduced as cinchonain formates.…”
Section: Resultsmentioning
confidence: 97%
“…Besides, it is one of the main ingredients of turtle jelly (Gui-ling-gao), a traditional functional food popular in Southern China and Hong Kong. Phytochemical studies have shown the presence of abundant compounds in S. glabrae , such as flavonoids, phenolic acids and phenylpropanoid glycosides [2,3], among which flavonoids were considered to be the primary bioactive constituents of the herbal medicine. Astilbin, neoastilbin, isoastilbin, neoisoastilbin, engeletin and isoengeletin were considered as marker constituents included in S. glabrae .…”
Section: Introductionmentioning
confidence: 99%
“…Some analytical methods have been used for qualitative or quantitative analysis of some of these bioactive constituents in S. glabrae . Li et al identified the main constituents in Rhizoma Smilacis glabrae by means of UHPLC-DAD-MS [3]. Chen et al established an HPLC method for determination of five compounds in Rhizoma Smilacis glabrae [11].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the excellent ability to analyse multiconstituents in complex matrices, HPLC-ESI/MS n has become a powerful approach for the rapid identification of constituents in TCM extracts (Zhang et al, 2012a(Zhang et al, , 2012b(Zhang et al, , 2013a. In this regard, a new hybrid linear trap quadrupole (LTQ) and orbitrap analytical platform is applied to the analysis of small molecules in biological and TCM samples (Zhu et al, 2007;Li et al, 2012;Xu et al, 2012). It consists of a two-dimensional ion trap coupled with an orbitrap, and allows two different scan types to be acquired simultaneously.…”
Section: Introductionmentioning
confidence: 99%